Ultrastable Response-Stimulus Synchronization: Acquisition, Stimulus Control, and a Model of Steady State Performance - Hopkns, Gordon Wayne (My University, 1982)
Human beings have a remarkable ability to accurately anticipate the time of occurrence of a predictable sensory event and synchronize an overt response with that event. Presumably this behaviour is mediated by central temporal mechanisms which are involved in timing the delay required to trigger the response at some precise point in time. It was the purpose of this investigation to examine the nature and functioning of these human temporal mechanisms. The basic task, modelled after Kristofferson (1976), involved presenting two brief stimuli, separated by a short time interval. Interstlmulus interval was fixed for a particular subject and the subject was instructed to anticipate the second stimulus, timing from the first, in order to trigger a response which would be manifested in synchrony with onset of the second stimulus. Several modifications were made to this basic response-stimulus synchronization procedure, which included subject-paced trials, and provision of highly salient feedback. These modifications resulted in a significant reduction in the lowest, previous estimate of minimum response latency variance. Minimum variances under 35 msec2 were obtained and the data indicated that response latency variance was independent of mean latency over a range of synchronization intervals from 310 to 550 msec. Within this range, latency distributions were the same, symmetrical, and sharp-peaked, unlike typical reaction time. All responses fell within a 50 msec time window. This independence of mean latency and latency variance was present throughout acquisition. A special technique allowed isolation of the controlling stimuli used for synchronization timing and showed that, in some situations, subjects were able to transfer timing control for synchronization responding from one modality to another with no loss of performance. This was true when transferring between auditory and tactile modalities, but not when visual interval markers were employed. A study of these dissimilar intra-modality findings, using a simple reaction time procedure, suggested that the differences could be attributed to a large afferent latency variance associated with visual stimulation which was not inherent in the other modalities. The role of feedback in acquisition and maintenance of synchronization performance was also examined, using manipulations which either selectively removed a particular source of feedback or altered the integrity of the feedback information. These manipulations provided data which indicated feedback to be one of the most important factors responsible for producing ultrastable stimulus-response latencies variance. and maintaining low The other important levels of response latency factor appears to be prolonged practice at a particular synchronization interval. Results are discussed in terms of support for the notion of nonvariable, centrally-timed delays which can be inserted into the stimulus-response chain. These delays are easily adjustable, but once set, are deterministic. A formal, mathematical model was formulated which describes the response-stimulus synchronization data remarkably well and provides a well-defined theoretical framework for conceptualizing this type of behaviour. From the model, independent variance estimates were derived for both central and efferent components in the stimulus-response chain. Values obtained are consistent with previous estimates derived from quite diverse methodologies in the literature. The model also provided some insight into what changes in processing occur during acquisition of this skill.
Keywords: Psychology; Psychology